2015
DOI: 10.1111/jth.12785
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of fibrinogen αC regions and their arrangement during fibrin network formation by high‐resolution AFM

Abstract: To cite this article: Protopopova AD, Barinov NA, Zavyalova EG, Kopylov AM, Sergienko VI, Klinov DV. Visualization of fibrinogen aC regions and their arrangement during fibrin network formation by high-resolution AFM. J Thromb Haemost 2015; 13: 570-9.See also Rocco M, Weisel JW. Exposed: the elusive aC regions in fibrinogen, fibrin protofibrils and fibers. This issue, pp 567-9.Summary. Background: Fibrinogen has been intensively studied with transmission electron microscopy and x-ray diffraction. But until now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 42 publications
(74 reference statements)
12
81
0
Order By: Relevance
“…We conclude that FXIII induced cross-linking is not responsible for bond formation. Instead, we propose that bond formation is facilitated by noncovalent interactions, most likely mediated by the unstructured αC-regions, two long and flexible chains attached to the distal ends of each fibrin monomer 44 . Specific interactions between these chains mediate lateral association of protofibrils into fibers as well as interactions between fibrin fibers 45 (see schematic in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We conclude that FXIII induced cross-linking is not responsible for bond formation. Instead, we propose that bond formation is facilitated by noncovalent interactions, most likely mediated by the unstructured αC-regions, two long and flexible chains attached to the distal ends of each fibrin monomer 44 . Specific interactions between these chains mediate lateral association of protofibrils into fibers as well as interactions between fibrin fibers 45 (see schematic in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…28,29 The aC region of fibrinogen contributes its own critical roles in the assembly and properties of clot structure. 8,[30][31][32][33] This region has also been directly correlated with adhesion events. [34][35][36] Fibrinogen aC region (221-610) is composed of a flexible aC connector (221-391) and a more structured aC domain (392-610).…”
Section: Introductionmentioning
confidence: 95%
“…4,7 During fibrin polymerization, crosslinking in the aC region has been shown to promote lateral aggregation and protofibril staggering. 8,30,37 Studies with native fibrinogen vs the mutant (gQ398N, gQ399N, and gK406R) have revealed independent contributions coming from a-a crosslinks. 16,38 Such crosslinks play major roles in promoting clot stiffness, fiber straightening, and hindering fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…26,31,58,87,88 This region has also been directly correlated with adhesion events. [89][90][91] Fibrinogen αC region (221-610) is composed of a flexible αC connector (221-391) and a more structured αC domain (392-610).…”
Section: 86mentioning
confidence: 98%
“…Prior to fibrin polymerization, the αC region is tethered to the central E region. 30,31 Fibrinogen is converted to active fibrin upon thrombin cleavage of fibrinopeptides A and B, on the Aα and Bβ chains respectively. Cleavage of fibrinopeptides A and B initiates fibrin polymerization by exposing knobs "a" and "b" in the central E region which interact with the complementary holes "A" and "B" in the D region of another fibrin molecule.…”
Section: -30mentioning
confidence: 99%